The pretender and the philosopher: : a brief essay of ut pictura poesis - Oliveira, Ana Lúcia M. de (2017)
This article takes into account the parallel between painting and discursive arts in its Greek philosophical confi guration. In considering Plato’s dialogues, the focus of the analysis will be the comparison between rhetoric or poetry and painting in order to detect its anti-sophistic motivations as well as the Platonic theory of mimetic representation. The investigation will emphasize the relevant criteria of the distance in relation to truth, which constitutes not only a common aspect of the different mimetic arts but also a cause for their disqualifi cation by the philosopher